A new cryptic rock-dwelling Hemidactylus (Squamata: Gekkonidae) from south India - Agarwal, Ishan; Giri, Varad B.; Bauer, Aaron M. (Zootaxa, 2011)
A new species of gecko, Hemidactylus graniticolus sp. nov. is described from Karnataka state, south India. This largesized (SVL to at least 110.6 mm), rupicolous gecko differs from congeners in having 16–18 longitudinal rows of fairly regularly arranged, subtrihedral, weakly keeled, striated tubercles at midbody; 9–11 and 12–13 subdigital lamellae on the first and fourth digits, respectively, of both manus and pes; tail with transverse series of four enlarged tubercles on each tail segment; 23–28 femoral pores on each side separated by 1–3 poreless scales; 12–14 supralabials and 9–11 infralabials. Molecular data support the distinctiveness of the new species and its affinities with large-bodied, tuberculate Hemidactylus spp. from India and Sri Lanka.